Productive Specialization and Relational Analysis: The Automotive Industry in Guanajuato - Adriana MARTÍNEZ MARTÍNEZ; Gabriel SANTOS NAVARRO; Alejandro GARCÍA GARNICA (El Colegio de la Frontera Norte, A.C., 2017)
The main objective of this paper is to measure, on the basis of the Economic Censuses 2004, 2009 and 2014, as well as 2008 Input-Output Matrix, the productive specialization using the location coefficient and the relational analysis of the automotive industry in Guanajua to. The main findings are an increasing specialization of some economic activities and a perma - nence of a low level of contribution of locally produced inputs. All of this opens up signifi - cant challenges for industrial policy in this region.